Oral leukoplakia: A review of clinical features and trends in management - Pandita Vaibhav; Ajila Vidya; Babu Subhas; Hegde Shruthi (Medicinski fakultet i Klinika za stomatologiju, Niš, 2022)
Introduction: Oral potentially malignant disorders (OPMD) conisit of the group of diseases of great importance for dentists. Oral leukoplakia (OL) has long been the subject of debate by numerous researchers. A common etiologic factor is tobacco, which is associated with oral cancer. The aim of the study is to indicate the severity of the lesion, the most common clinical characreistics and localization. The prevalence of leukoplakia in the world is 2.6% with a rate of malignant conversion ranging from 0.1% to 17.5%. Literature data about the prevalence and annual rate of malignant transformation, approximately 2%, indicate that these changes should be taken seriously and regularymonitored Conclusion: Occurate diagnosis provides the key to preventing to malignant transformation. Various medical and surgical treatment modalities for this lesion have been described. This article highlights various trends in the diagnosis and treatment of oral leukoplakia.